Choice of Islamic Law in Settlement of International Economic Disputes - Helza Nova Lita; Norazlina Abdul Azis; Adnan Mahmutovic; Nun Harrieti; Romidon Hidayat (Lex Scientia Law Review, 2024)
The freedom to choose forum institutions and legal options in resolving business disputes is a freedom to contract exercised by national and international business actors, likewise in settling Islamic economic business disputes. This freedom of contract is recognized both in the principles of international trade law and Islamic law. The present development of sharia business transactions at the national and international levels does not rule out the possibility of disputes in its implementation. The consistency of implementing Islamic economics also concerns the choice of Islamic law, which is used as a choice of law for international business actors in case of a dispute between them. Studying how specific Islamic law can be applied to each country's national law is interesting. This article will discuss how Islamic law can be chosen to settle international business disputes using a normative juridical approach. Choice of law is the law the parties choose to resolve disputes between them, which can be expressed in their business contracts. The choice of law chosen by these parties in the settlement of international business disputes will also be closely related to the principles of Private International Law in harmonizing with the provisions of the National Law of each country. There needs to be mutual agreement from both countries, as well as international forums or institutions, especially international trade institutions, to support the recognition of the application of Islamic legal principles in resolving international business disputes through international agreements both bilaterally and multilaterally.